(untitled) (Latakia University Journal -Basic Sciences Series, 2016)
تصف هذه الدراسة التغيرات الحاصلة في تراكيز الكلوروفيل، أ و الملوثات الهيدروكربونية في منطقة ميناء اللاذقية خلال الفترة الممتدة من شهر شباط عام 2011 حتى شهر كانون الأول من العام نفسه. تناسبت تراكيز أ الكلوروفيل بشكل طردي مع تراكيز الملوثات الأليفاتية في المحطات القريبة من الشاطئ والمعرضة بشكل مستمرّ للملوثات الهيدركربونية وتناسبت هذه التراكيز بشكل عكسي مع تراكيز الملوثات العطرية و ، كما ترافقت تراكيز الكلوروفيل أ بقيم منخفضة لمؤشر التحلل الحيوي ، ممّا يدل على نشاط بكتيري تفكيكي مرتفع في هذه المنطقة. بلغت القيمة العظمى لتراكيز الكلوروفيل أ 6.33 mg. m-3 في المحطة على بعد 300م في شهر آب ، بينما سجلت القيمة الادنى في المحطة التي تقع على بعد 1500م في شهر تشرين الأول وبلغت 0.07 mg.m-3 تراوحت تراكيز مركبات الـACHs دون عتبة الكشف (not detected) و186.351μg/l ، و مركبات الـPAHs دون عتبة الكشف (not detected) و24.539μg/l، حيث سجلت أعلى التراكيز في المحطات القريبة من الشاطئ، وأقلها في المحطات البعيدة عنه. This study describes the changes in the concentrations of chlorophyll a and hydrocarbon contaminants in the port of Latakia during the period from February 2011 to December in the same year. The chlorophyll a concentrations are proportional with the concentrations of aliphatic pollutants at the stations near the beach which exposed continuously to Hydrocarbon Contaminants, also , this chlorophyll a concentration was accompaused by the lew concentrations of aromatic pollutants, and chlorophyll a concentrations accompanied by the low values ​​of the index biodegradation, that suggest existing deconstructive high bacterial activity in this region. Higher value of concentrations of chlorophyll a was 6.33 mg. m-3 at the station, which is 300 m away from the beach in August, while the lowest value recorded in the station, which is 1500 m away from the beach in October and it was 0.07 mg.m-3 The concentrations of aliphatic compounds ranged between (below the threshold of detection -not detected- ) and 186.351μg / l and PAHs compounds ranged between (below the threshold of detection -not detected- ) and 24.539μg / l. The highest concentrations were detected at stations near the beach and the least were away from beach..